Dr. L. Scott Ennis — Deep Plane Facelift — Boca Raton - Ennis, L. Scott (DEEPPLANE™, 2026)
Surgeon profile record for Dr. L. Scott Ennis, practicing in Boca Raton, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002981; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; boca raton